BALKAR MOUNTAIN SOCIETIES WITHIN THE CONTEXT OF THE IMPERIAL MODERNIZATION OF RUSSIA: ETHNOSOCIAL CONSOLIDATION AND DEVELOPMENT - E. G. MURATOVA (Кавказология, 2019)
The article deals with some aspects of development of the Balkar mountain societies in the conditions of Imperial modernization of Russia. It is based on archival sources of the 19th – early 20th century from the Russian State Military Historical Archive (RGVIA), the Russian State Historical Archive (RGIA), the St. Petersburg branch of the Archive of Russian Academy of Sciences (SPb.FA RAN), the Central State Archive of the Kabardino-Balkar Republic (CGA KBR), the Central State Archive of the Republic of North Ossetia-Alania (CGA RSO-Alaniya). The source base is supplemented by legislative acts and periodicals on the topic of the study. These sources allow depict the history of Balkaria during its political and socio cultural integration into the Russian Empire. It is proposed an original interpretation of the specific features of realization of administrative and judicial reforms of the 19th century in Balkar societies as transformations carried out taking into account the specifics of local conditions and contributed to their ethno-social consolidation. The development of communications, the formation of social infrastructure and new forms of economic activity in mountain societies of the post-reform period are shown. Based on the materials of mass historical sources, the study of the demographic and socio-economic structure and evolution of Balkarian rural societies by the beginning of the 20th century was carried out. The analysis of the considered issues leads to the conclusion that the source of the historical dynamics of the Balkar society, the transformations that it underwent during the 19th and early 20th centuries, was the policy of the Russian state in the Caucasus and its impact on the internal life of local societies. Gradually, the mountain community got more and more «open character». The society to go beyond local communities, acquiring its own social scale corresponding to ethnic boundaries. The paper presents a description of the local model of traditional society in the transit to modernity.  The research results are indispensable for writing a generalizing work on the problem of integration of such a culturally complex macro-region as the North Caucasus into the Russian state area.